PERPUSTAKAAN DENGAN KONSEP MAKERSPACE DI BANJARBARU - Kubra, Dhea Yaumil Haz; Heldiansyah, JC (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Libraries have an important role in society as places that support education, research, culture, access to information, as well as in maintaining and preserving cultural and intellectual heritage. Now we have entered an era of digital disruption caused by technological advances that provide easy access to search for information via the internet, but technological developments have an influence on visitors' interest in visiting libraries. One of the problems in Banjarbaru City is the lack of quality competitive human resources, such as the problem of not achieving the quality of public education according to standards, while educational support facilities such as libraries are still rarely visited. So far, the library is an unattractive place to visit because of the limited activities that can be done in the library. Efforts that can be made to increase interest in coming to the library are changing views about libraries by making libraries able to collaborate or combine activities within them by utilizing technology as support. The application of the makerspace concept in a library is effective for combining various activities or programs and can be carried out simultaneously. The collaborative space method is used as a problem solving process with the main aim of collaborative space design being to create an environment that supports various types of group activities. The concept of interactive architecture is used to support collaborative space methods so that building design can play a role in the variety of human activities accommodated in a building.